Lactobacillus plantarum OLL2712 induces IL-10 production by intestinal dendritic cells - TAKANO, Tomohiro; ENDO, Ryunosuke; WANG, Yimei; NAKAJIMA-ADACHI, Haruyo; HACHIMURA, Satoshi (Bioscience of Microbiota, Food and Health, 2020)
Recently many researchers have revealed that certain lactic acid bacteria (LAB) have beneficial effects on the immune system. Understanding the mechanisms of how certain LAB induce immunomodulatory functions is important for the development of food ingredients that improve our health. Lactobacillus plantarum OLL2712 has been shown to induce production of interleukin (IL)-10, an anti-inflammatory cytokine, by murine in vitro-induced dendritic cells (DCs) and peritoneal macrophages. However, it is probable that in vitro-induced DCs have different properties compared with intestinal DCs, and the effects of the LAB on intestinal DCs are not fully understood. In this report, we investigated whether L. plantarum OLL2712 had efficacy for inducing intestinal DCs to produce IL-10 in vitro and whether oral administration of the bacteria induced the same effect. Co-culture of L. plantarum OLL2712 with purified DCs from the mesenteric lymph node (MLN) or Peyer’s patch (PP) elevated IL-10 mRNA expression and protein production by both kinds of DCs. Addition of the LAB enhanced IL-10 production by T cells during antigen-specific responses in co-culture of MLN or PP DCs and T cells. Oral administration of L. plantarum OLL2712 for 6 days increased IL-10 gene expression in MLN DCs, and upregulated IL-10 gene expression in PP DCs was observed 12 hr after oral administration of the LAB. Our results suggested that L. plantarum OLL2712 could modulate immune responses by enhancing IL-10 production from intestinal DCs.